(untitled) (Costos y Gestión, 2021)
Pursuing the ultimate goal of contributing to reducing the marked strategic deficit that denotes most of the familiars SME, which are of paramount importance for the development of regional economies in current scenarios, a Balanced Scorecard (BSC) is designed considering the stakeholder’s expectations holistically, within a social responsible framework. Through a theoretical review of the bibliography related to Strategic Management, BSC, and Stakeholder Theory, potentialities of the tool are highlighted by describing the evolution of Kaplan and Norton’s initial proposal. On the other hand, critics and limitations that other authors indicated against it, are systematized in three axes: Firstly, those that question its applicability to certain types of organizations; secondly, those that point out the excessive simplicity at the time of analyzing the logical relations between the objectives; last but not least, those that emphasize the bias towards satisfying the interests of a specific group. Under these guidelines, an alternative model of a «Wheel BSC» is proposed, with the concept of value at the center, as the goal to be maximized for all stakeholders, who are represented in the different perspectives. In addition to this, the analysis of the logical relationships between the objectives is deepened by a mental model that contemplates the dynamic of complex systems, as it is the case of organizations. The application of this technique (BSC) is approached with a strategic management focus, under the paradigm of the Stakeholder Theory, that seeks a new business mindset, bridging concepts of ethics and business inseparably, in pursuit of a long term sustainable development.